Time Series Properties of Some Climatic Variables in Dinajpur District - Rahman, MJ; Syeda, JA; Nasser, M (Journal of Environmental Science and Natural Resources, 2015)
Several direct empirical time series investigations of global climate change and its impact have been studied by several world famous researchers. Some researches regarding local climatic change and its impact have been published but the time series properties of the variables related to national as well as local climate are yet to be able to have proper attention. The presence or absence of unit roots in these time series or inappropriate statistical tools may challenge the validity of the interpretations of their results and implies that cointegration analysis can be used to investigate the relation among variables. This article attempts to deduce time series properties of temperature, rainfall and humidity of Dinajpur district. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22109 J. Environ. Sci. & Natural Resources, 6(2): 127-137 2013